EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DALAM PELAKSANAAN KURIKULUM 2004 PADA SMA PILOTING DI DAERAH ISTIMEWA YOGYAKARTA (HEADMASTERS’ LEADERSHIP, ITS EFFECTIVENNESS AND ROLE TOWARD THE IMPLEMENTATION OF CURICULUM 2004 UPON SOME HIGH SCHOOL OF YOGYAKARTA) - Trikinasih Handayani; M. Joko Susilo (Bioedukasi: Jurnal Pendidikan Biologi, 2006)
This research was aimed to know the effectivenness of headmaster’s leadership toward the implementation of curiculum 2004. This research focused on the the integrity of the headmaste, his ability on overcoming the institution’s problems and his leadership style and related them with the leadership’s effectivenessin in carrying the implementation of the curiculum 2004. This research was carried out at SMAN 7 Yogyakarta, SMAN 11 Yogyakarta, SMAN Sewon and SMAN Kalasan. The data collected by anquette were analyzed by double regression and Pearson’s correlation using SPSS release 10. Intepretation was then made descriptivelly.The results showed that all, the integrity, ability to solve the institution’s problems, and the ladership style of the headmaster, together, affected the leadership’s effectiveness of the headmaster during implementation of curiculum 2004.